International partnership at tourist services market - Volodymyr Mazur (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The article deals with the following levels of realization of stages of the development of forms of international economic relations: international economic interaction, international economic contacts, international economic cooperation and international economic integration.